Perancangan 5S pada Area Packing di PT Charoen Pokphand Indonesia Feedmill Balaraja - Vincent Handoyo; Jani Rahardjo (Jurnal Titra, 2018)
PT Charoen Pokphand Indonesia Feedmill Balaraja is a company that engaged in the manufacture of animal feed. The probelm that faced by PT Charoen Pokphand  Indonesia Feedmill Balaraja they have not applied the concept of 5S in packing area. Stuff, tools and machines in packing area have not been neatly arranged, so it will make difficulty for operators or workers in finding something they need. This thesis will be used for helping in design and implementation the concept of 5S in PT Charoen Pokphand Indonesia Feedmill Balaraja packing area. The purpose of this thesis is to create a neat work area, so it will facilitate operators or workers in their activity.